Port Sunlight, essai architectural et social - Laurence Machet (Cahiers Victoriens et Edouardiens)
The purpose of this article is to examine the city of Port Sunlight, its history, design and originality. Created by William Lever in 1888 in order to house his newly-built soap factory, Port Sunlight is part of the numerous “factory villages” built in the wake of the industrial revolution according to philanthropic and utilitarian principles. But this article intends to show that Port Sunlight differs from other factory towns. Its careful design, elaborate architecture and public facilities epitomize the aesthetic and philosophical trends of the period and reveal a strongly ambivalent attitude towards industry and the type of landscapes it had created. Announcing Ebenezer Howard’s garden cities, Port Sunlight endeavours to solve the material problem of working class housing while also addressing other more spiritual needs.